(untitled) (Research, Society and Development, 2021)
Currently, tooth whitening is one of the procedures most sought by patients in cosmetic dentistry. In view of the variety of techniques available, it is necessary for the dentist to be able to choose the best method to achieve the clinical success of this procedure. Objective: To carry out an integrative literature review, with an emphasis on clinical studies on tooth whitening in dental clinics and to answer the guiding question, in addition to presenting the best methods for clinical success. Methodology: This is an integrative review of the literature of a qualitative nature based on the guiding question: what are the main aspects for a clinical success in the management of tooth whitening in the dental clinic? The databases were: US National Library of Medicine (NLM - PubMed) and Science Health and Medical Journals (ScienceDirect), using the following descriptors in English found in Health Sciences Descriptors (Decs): Tooth Bleaching, Tooth Bleaching Agents and Methods. The inclusion criteria were articles published in English, Portuguese and Spanish; publications between January 2020 and January 2021 and that addressed the topic in a satisfactory manner. Articles that did not meet the inclusion criteria were excluded. 3,761 articles were found in full, after application of the inclusion criteria and specialized reading, 14 articles were selected. Results and Discussion: It was found that to achieve the clinical success of tooth whitening, it is necessary to evaluate factors intrinsic or extrinsic to the whitening agent: Violet LED light (405–410nm) can improve the effectiveness of tooth whitening, without increasing sensitivity; the addition of NaF / TMP in the office, whitening did not interfere in the efficacy of whitening, reduced demineralization, penetration, cytotoxicity, and the morphological cellular alteration was intense for all bleaching gels; the discoloration of the MTA was improved equally well between pre-application of the DBA and post-bleaching; In relation to whitening toothpaste, the higher pH produces a better shade change; 10%, before in-office whitening, did not reduce the risk and intensity of tooth sensitivity and did not impair the color change; the laser did not improve the results compared to not using a laser during bleaching; the polishing of the samples caused significant changes in the rate of depolarization and anisotropy of the symmetric phosphate elongation band, and increased the rate of demineralization; high volume resin showed a small color change; ProRoot white MTA tends to cause black and blue discoloration. SavDen MTA, formulated with calcium lactate gluconate, can be used to reduce discoloration of teeth in endodontic treatment; bleaching agents were effective and showed a moderate influence on the patients’ aesthetic perception and psychosocial impact. Final Considerations: the use of ultraviolet light, the search for materials that offer less risk of decreasing the enamel hardness and the combination of home and office treatments contribute to the clinical success of tooth whitening.